PENGARUH LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN PT. SURYA PERDANA AGUNG PEKANBARU - Lamin, Lamin (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
Based on the results of the research analysis found the test results that t-count is greater than t-table (4.006> 2.042). Thus it can be concluded that the variable Non-Physical Work Environment (X) has a significant effect on the performance of employees of PT. Surya Perdana Agung Pekanbaru. The result of simple linear regression shows Y = a + bX that is: Y = 15,016 + 0,603 X. From the regression equation it is concluded that the regression coefficient of bx is positive. This indicates that independent variables if increased equation will cause an increase in the dependent variable. R Square results of 0.321 (32.1%) explained that the performance of employees of PT. Surya Perdana Agung Pekanbaru influenced by Non Physical work environment of 32.1% while the rest of 67.9% influenced by other independent variables not observed in this study